The use of plastics as a socio-scientific issue for developing critical thinking through argumentation with pre-service teachers. - Hierrezuelo-Osorio, José Manuel; Cebrián-Robles, Daniel; Brero-Peinado, Vito Battista; Franco-Mariscal, Antonio Joaquín (ASE International Journal, 2021)
The treatment of socio-scientific issues in the classroom using role-playing is a teaching strategy of greater interest for the development of critical thinking in pre-service teachers by way of scientific argumentation. This paper shows a role-playing activity to reflect on the elimination of plastic use, which was put into practice with 66 Spanish pre-service teachers taking the Degree in Primary Education at the University of Malaga (Spain). The game involved several roles in favour (ecologist, fisherman, minister of industry, bioplastics producer) and against (lobby, packaging chain consultant, frozen fish company executive and others), and used a questionnaire, before and after the activity, to analyse the participants’ understanding of plastics and their perceptions concerning the use of role- playing in the classroom. Our findings show how pre-service teachers progress in their understanding of basic concepts related to the properties of plastics and, although there was no significant change in their decisions regarding the production and consumption of plastic, the reasons given were slightly modified before and after the role play. Similarly, after participating in the activity, they were more predisposed to use this technique as a teaching strategy in the classroom, and they also exhibited greater confidence in defending their role.
Keywords: Ciencias - Estudio y enseñanza; Pensamiento crítico; Juegos de simulación en la enseñanza; Juegos de rol; Socio-scientific issues; Critical thinking; Role-playing